THE MEDIATING ROLE OF E-WORD OF MOUTH INTENTION IN THE RELATIONSHIP BETWEEN PLACE ATTACHMENT AND REVISIT INTENTION IN NOSTALGIA TOURISM - Sood, Payal; Gupta, Dikshit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: This study explores the relationships between place attachment, nostalgia tourism, and revisit intentions among international tourists visiting their ancestral hometowns, with a specific emphasis on the mediating role of electronic word-of-mouth (e-WOM). Methodology: A descriptive-causal research design was employed, and data were collected using convenience sampling from international tourists in regions with high Non-Resident Indian (NRI) populations, including Punjab, Delhi, Himachal Pradesh, and Chandigarh. A total of 430 valid responses were obtained and analyzed using Structural Equation Modeling (SEM) to assess both the measurement and structural models. Findings: The results indicate that both place identity and place dependence have a positive influence on e-WOM intentions and revisit intentions. Furthermore, e-WOM intentions were found to mediate the relationship between place attachment and revisit intentions. Implications: The study underscores the significant role of emotional and social connections to a place in shaping tourist behavior. Value These insights are particularly useful for tourism marketers and policymakers seeking to foster destination loyalty by leveraging the impact of place attachment and e-WOM.